Evaluation of brucellosis eradication strategies in water buffalo in a key dairy production area of southern Italy - Mascolo, Celestina; Mazzeo, Alessandra; Maiuro, Lucia; Signoriello, Simona; Ferrara, Carlo; Esposito, Marco; Rosati, Sebastiano; Sorrentino, Elena (Frontiers in Microbiology, 2026)
Brucellosis in water buffalo remains endemic in southern Italy, particularly in areas of the province of Caserta characterized by high animal density. This retrospective cohort study (2016–2021) assessed the effectiveness of stamping out (whole-herd depopulation) versus selective culling in counteracting brucellosis in water buffalo herds. Data from 222 outbreaks were analyzed using Cox regression, incorporating herd size, buffalo density, eradication method, and co-infection with Mycobacterium bovis. Stamping out reduced reinfection risk by 80% (HR = 0.2; p < 0.001), especially in municipalities exceeding 200 buffaloes/km2. Co-infection with M. bovis was not statistically associated with reinfection. These results indicate that control strategies should prioritize stamping out, coupled with reinforced structural and operational biosecurity measures, even in high-density settings, to achieve disease-free status. Integrated surveillance and education, in line with One Health principles, are essential for sustainable eradication and protection of the buffalo dairy sector.